Functional data analysis of the kinematics of gait in subjects with a history of achilles tendon injury - Donoghue,O.; Harrison, A. J.; Coffey, N.; Hayes, K. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Clinical biomechanics research aims to understand the mechanisms of injury to improve prediction, prevention and rehabilitation. Dynamical systems theory suggests that coordination and variability may be key issues in the development of injuries. Traditional analysis has relied on a multivariate approach using discrete measures during stance. This essentially discards kinematic data obtained throughout the entire stance phase. Functional data analysis is an established statistical technique that is now emerging in biomechanics. It views the data as a function, thus using the entire time series data and determines which factors contribute to the variation. The purpose of this study was to examine the predictions of dynamical systems theory on angular kinematic data in subjects with Achilles tendon injury using a functional data analysis approach.